Crisis of Imagination:: the ambivalence of the fantastic in Bécquer, Todorov and Blanchot - Gingerich, Stephen (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In philosophy, as in everyday life, we consider imagination most frequently as an enabling power, essential to perception, memory, and understanding. This essay examines theories and a literary example that define literature as a particular kind of failure of imagination. A sustained look at the concept of imagination shows that its history contains unexpected ambiguities and contradictions, such that it often appears to be a more a mystery than a method. In a reading of Gustavo Adolfo Bécquer’s well-known, fantastical legend “La cruz del diablo” (The Devil’s Cross), I elaborate the idea of a “wounded imagination,” relating the production of a literary text to the process of healing a wounded psyche. I then examine Tzvetan Todorov’s contention that fantastic literature provides a privileged place to observe the essence of literature, characterizing his ideas as an application of Maurice Blanchot’s profound meditations on literature.
Keywords: imagination; literture; fantastic; Gustavo Adolfo Bécquer; La cruz del diablo; Tzvetan Todorov; Maurice Blanchot